Malaria morbidity in Papua Indonesia, an area with multidrug resistant Plasmodium vivax and Plasmodium falciparum. - Karyana, M; Burdarm, L; Yeung, S; Kenangalem, E; Wariker, N; Maristela, R; Umana, K; Vemuri, R; Okoseray, M; Penttinen, P; Ebsworth, P; Sugiarto, P; et al. (BioMed Central, 2008)
BACKGROUND: Multidrug resistance has emerged to both Plasmodium vivax and Plasmodium falciparum and yet the comparative epidemiology of these infections is poorly defined. METHODS: All laboratory-confirmed episodes of malaria in Timika, Papua, Indonesia, presenting to community primary care clinics and an inpatient facility were reviewed over a two-year period. In addition information was gathered from a house-to-house survey to quantify the prevalence of malaria and treatment-seeking behaviour of people with fever. RESULTS: Between January 2004 and December 2005, 99,158 laboratory-confirmed episodes of malaria were reported, of which 58% (57,938) were attributable to P. falciparum and 37% (36,471) to P. vivax. Malaria was most likely to be attributable to pure P. vivax in children under one year of age (55% 2,684/4,889). In the household survey, the prevalence of asexual parasitaemia was 7.5% (290/3,890) for P. falciparum and 6.4% (248/3,890) for P. vivax. The prevalence of P. falciparum infection peaked in young adults aged 15-25 years (9.8% 69/707), compared to P. vivax infection which peaked in children aged 1 to 4 years (9.5% 61/642). Overall 35% (1,813/5,255) of people questioned reported a febrile episode in the preceding month. Of the 60% of people who were estimated to have had malaria, only 39% would have been detected by the surveillance network. The overall incidence of malaria was therefore estimated as 876 per 1,000 per year (Range: 711-906). CONCLUSION: In this region of multidrug-resistant P. vivax and P. falciparum, both species are associated with substantial morbidity, but with significant differences in the age-related risk of infection.